Identificación de un brote de SARSCoV-2 (Covid-19) en un centro gerontológico de la Ciudad de México - Alejandro Hernández-Solis; Ana Karen Solís-Zúñiga; Marcos Enrique Salgado-Carrillo; María de Guadalupe Juárez-Hernández; Pablo Álvarez-Maldonado; Arturo Reding-Bernal (Instituto Nacional de Salud Pública, 2021)
Objective: To describe a Covid-19 outbreak in a gerontological center in Mexico City. Material and methods: Cross-sectional study in older adults. The association of risk factors for dying from Covid-19 was analyzed using a multiple logistic regression model. Results: One hundred and two elders with an average age of 82.5 ± 8.8 years were included. Fifty-five (54%) tested positive and 47 (46%) were negative for the new coronavirus. Using the multiple logistic regression model, people with frailty had an OR of 11.6 of dying from Covid-19 compared to robust people (p-value = 0.024). Conclusion: The Covid-19 outbreak was initially caused by a resident of the center and spread by cross infection. In vulnerable populations, early detection, isolation, and follow-up of contacts should be carried out, as well as the identification of risk factors in order to reduce the spread and mortality caused by SARSCoV-2.